Complementarities in information acquisition with short-term trades - Christophe Chamley (Theoretical Economics, 2007)
In a financial market where agents trade for short-term profit and where news can increase the uncertainty of the public belief, there are strategic complementarities in the acquisition of private information and, if the cost of information is sufficiently small, a continuum of equilibrium strategies. Imperfect observation of past prices reduces the continuum of Nash equilibria to a Strongly Rational-Expectations Equilibrium. In that equilibrium, there are two sharply different regimes for the evolution of the price, the volume of trade, and information acquisition.
Keywords: D53; D82; D83; G14; 330; Endogenous information; short-term gain; microstructure; strategic complementarity; multiple equilibria; Strongly Rational-Expectations Equilibrium; trading frenzies